CRITICAL SUCCESS FACTORS (CSF) FOR THE ISO 9001 IMPLEMENTATION IN UIN SUNAN KALIJAGA YOGYAKARTA - Kifayah Amar (Kaunia: Integration and Interconnection Islam and Science, 2012)
This study attempts to identify factors that are considered critical for the implementation of ISO 9001 in UIN Sunan Kalijaga Yogyakarta. In this study, data were obtained from interview and observation of documents related to the implementation of ISO 9001 in UIN Sunan Kalijaga Yogyakarta. The content analysis was used as an interpretation method for qualitative interviews data. Finding shows a number of factors that are considered critical in the implementation of ISO 9001. They are top management commitment and support, training, culture change, continuous improvement and performance measurement. Top management commitment and support is an important role for the success and sustainability of ISO 9001. The support can be in a form of their active participation in quality management activities. In addition, the provision of adequate resources as well as supporting quality policies is also critical for the ISO 9001 implementation in UIN Sunan Kalijaga. The other critical factor is the culture change that perceived as a strong foundation for the success of ISO 9001 implementation.